Polymer nanoclay composites - Laske, Stephan (Micro & nano technologies., 2015)
There is a major lack of fundamental knowledge and understanding on the interaction between a filler and the polymer matrix. When it comes to nanoscale fillers, such as layered silicates, carbon nanotubes, graphene or cellulose nanofibers it is even more important to know accurate structure-property relationships as well as identifying the parameters influencing material behavior. The reason for the lack of knowledge on how to process nanocomposites and why there are so few applications is that several scientific fields are affected and a joint effort of those scientific communities involved is necessary - starting from the filler manufacturing or pre-processing over polymer chemistry to the polymer processing. In Polymer Nanoclay Composites, all involved scientific areas are viewed together for the first time, providing an all-embracing coverage of all stages of polymer clay nanocomposites processing from lab-scale to industrial scale - stages from the raw material over manufacturing of polymer clay nanocomposites to characterization and the final products. Readers will gain insight in the physical/chemical pre-processing of layered silicates and their incorporation into a polymer matrix using sophisticated technologies (such as advanced compounding) as well as in real-time quality control of the nanocomposite production and future prospects. The book also describes nanotoxicological and nanosafety aspects. Covers the whole processing route with all aspects of the nanocomposites industry with particular focus on the processing of polymer clay nanocomposites Includes quality control and nanosafety Multidisciplinary approach from an industrial perspective.